Effect of Piper crocatum Extract on Kidney Histopathology in Alloxan-Induced Wistar White Rats (Rattus norvegicus) - Solfaine, Rondius; Rahmadhani, Diyana (Faculty of Veterinary Medicine Universitas Brawijaya, 2024)
The prevalence of diabetes mellitus is steadily increasing. According to the International Diabetes Federation in 2021, the number of diabetes sufferers in Indonesia has rapidly increased in the last ten years. This study aims to determine the effect of red betel leaf extract (Piper crocatum) on kidney histopathology of Wistar white rats (Rattus norvegicus) induced by alloxan. A total of 25 white male Wistar rats aged ± 3 months were used in this study. All samples were divided randomly into five treatment groups, namely: (K-) healthy rats that were only given distilled water; (K+) given a single dose of alloxan 120 mg/kg bw/intraperitoneal; (P1) rats given alloxan 120 mg/kgbw/intraperitoneally and red betel leaf extract 100 mg/kg bw/orally; (P2) rats given alloxan 120 mg/kg bw/intraperitoneally and red betel leaf extract 150 mg/kg bw/orally; (P3) rats were given alloxan 120 mg/kgbw/intraperitoneally and red betel leaf extract 200 mg/kg bw/orally. Treatment was given for 14 days. Blood glucose levels were measured using the Glucometer (EZ Smart) colorimeter method. On the day 15th, all rat were euthanized and necropsied to remove the kidneys and then made into preparations with HE staining. The histopathological lesions observed were necrosis, degeneration, and inflammatory cell infiltration. Histopathological observations were carried out using a microscope with 40x magnification. Data resulting from observations were analyzed using SPSS 20 with Kruskal-Wallis and Mann-Whitney (P≤0.05). It revealed that red betel leaf extract has a potential ability to reduce the effects of hyperglycemia, and by inducing 2% of red betel leaf extract at dose of 100 mg/kg bw, 150 mg/kg bw, and 200 mg/kg bw could reduce necrosis, inflammatory cell infiltration, and degeneration significantly in the kidneys of white rats.